Lenkų–jotvingių žodynėlis? (tęsinys) - Zinkevičius, Zigmas (Baltistica, 1985)
A Polish–Yatvingian vocabulary? The article examines the manuscript of a Polish–Yatvingian vocabulary (?) “Pogańske gwary z Narewu” found in 1978 by V. Zinov on a homestead in the forest of Belovezh (Byelorussian SSR). The extant copy of the vocabulary (the original has been lost) is published. The author presents in alphabetical order the list of all the Baltic words with reference to their counterparts in related languages as well as etymological and other observations. The phonetic and morphological structure of the words are analysed, and extralinguistic conditions as well as the complicated linguistic situation which existed in the area of Narev in the 13th–16th century are described. Concerning the Baltic nature of the words presented in the vocabulary, the author puts forward three solutions: 1) the words given in the vocabulary belong to the local Yatvingian dialect which has been subjected to the influence of the Lithuanian language; 2) the given words are Lithuanian; they have grown on the extremely strong Yatvingian substratum; 3) the person who compiled the vocabulary may have been unable to differentiate Yatvingian words from corresponding Lithuanian words and, consequently, may have included words of the two languages which at the time were to a large extent indistinguishable.